2018
DOI: 10.1016/j.anr.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Violence from the Clients and Coping Methods Among Intensive Care Unit Nurses Working in a Hospital in South Korea

Abstract: While intensive care nurses experience unpredicted violence from patients and their visitors, they fail to cope well with the experience. The safe working environment of intensive care units is expected to contribute to quality care and an improvement of expertise in nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…However, a higher prevalence of gastrointestinal problems, respiratory symptoms, headaches and sleeping problems was found among workers who had undergone violent situations in the workplace than those who had not. This finding agrees with previous studies which have reported health problems of nurses who had been victims of job violence 9 28 43…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, a higher prevalence of gastrointestinal problems, respiratory symptoms, headaches and sleeping problems was found among workers who had undergone violent situations in the workplace than those who had not. This finding agrees with previous studies which have reported health problems of nurses who had been victims of job violence 9 28 43…”
Section: Discussionsupporting
confidence: 93%
“…The most common strategies and responses professionals use to cope with violent situations are to request help from a coworker, warn the hospital security chief28 or tell a coworker about the violent incident later 18. Nurses consider improving communication with patients and the information given them, and enlarging the staff to be the most useful measures for reducing aggression in the workplace 18.…”
Section: Introductionmentioning
confidence: 99%
“…Further, many kinds of research supported this result: The study in Chinese clarify that workplace violence against nurses (93.5%) in Chinese hospitals Jiao et al (2015) and similar to the study in Saudi Arabia (71.7%) Algwaiz and Alghanim (2012) and correspondingly, a study in Iran (Esmaeilpour et al, 2011). Furthermore, in the survey, by Yoo et al (2018) found that 67.5% of the nurses agree that they had experienced violence from their visitors (families or relatives). Verbal violence was reported more than physical ones.…”
Section: What Is the Level Of Anxiety Regarding Workplace Violence Amsupporting
confidence: 57%
“…These nurses should be in contact with workers from different treatment units and keep up their knowledge with the state-of-art medical and remedial technologies. Therefore, they are under higher pressure compared to other nurses (6).…”
mentioning
confidence: 99%